Prix de Rome 1992 : Beeldhouwen / Beeldende kunst en openbaarheid. - Coelewij, Leontine; Fortuyn, Irene; Kaiser, Franz W.; Pitz, Hermann; de Baan, Christine; van de Pavert, Jan; de Vries, Auke; van den Boogerd, Dominic; van den Dobbelsteen, Jan; Museum Fodor, Amsterdam; Rijksakademie van beeldende kunsten, Amsterdam (Rotterdam : Uitgeverij 010, 1992)
Arink, Karin ; Claassen, Tom ; Drummen, Suzan ; Kinoshita, Suchan ; Kool, Renée ; Lancel, Arjen ; Leijenaar, Jorgen ; van Lieshout, Joep ; Manders, Mark ; Oude Alink, Karen ; Pollack, Linda ; Rikken, Miranda ; De Rooy, Noor ; Sonnemans, Petry ; Staals, Marlène ; Verhoeven, Frank ; Vos, Giny ; van Warmerdam, Marijke
biog. Karin Arink, Tom Claassen, Joep Van Lieshout, Marlene Staals, Suchan Kinoshita, Mark Manders, Noor de Rooy, Marijke van Warmerdam p. 106-107
Prix de Rome 1992 : Beeldhouwen / Beeldende kunst en openbaarheid, organisatie: Rijksakademie van beeldende kunsten, Amsterdam, tentoonstelling: Museum Fodor, Amsterdam, 05.11.1992 - 29.11.1992
Nederlands & Engels
boek